IMPLEMENTASI MANAJEMEN PENDIDIKAN ISLAM DALAM KONSEP MANAJEMEN HUBUNGAN MASYARAKAT DENGAN SEKOLAH - Rais, Wendi (LPPM STIE Pertiba, 2019)
The most important thing in the management of Islamic education is the management components. One of them is public relations management (public relations) because the school is in the midst of the community and always relates to establishing pedagogical and sociological cooperation that benefits both parties. Management is very important for the success of an organization. PR is a series of organized activities such as a series of integrated campaigns or programs, and all of them are ongoing and regular. The community as a third educational institution after family and school has a considerable role in the ongoing activities concerning education problems. Given the importance of the role of public relations in educational institutions and the gap between theory and reality in the field (problems), this paper will discuss